2014
DOI: 10.1111/jre.12158
|View full text |Cite
|
Sign up to set email alerts
|

Wnt signaling regulates homeostasis of the periodontal ligament

Abstract: Background and Objective In health, the periodontal ligament maintains a constant width throughout an organism’s lifetime. The molecular signals responsible for maintaining homeostatic control over the periodontal ligament are unknown. The purpose of this study was to investigate the role of Wnt signaling in this process by removing an essential chaperone protein, Wntless (Wls) from odontoblasts and cementoblasts, and observing the effects of Wnt depletion on cells of the periodontal complex. Material and Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
67
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(70 citation statements)
references
References 57 publications
(75 reference statements)
3
67
0
Order By: Relevance
“…It is not clear if β-catenin is responsible for bone maintenance in response to loading, plays a role in mechanotransduction in alveolar bone around teeth, or plays a role in the functions of the PDL. Supporting evidence shows β-catenin expression in the PDL in mice (Lim et al, 2014, Premaraj et al, 2011) in addition to being present in osteocytes and cementocytes. A recent study using PDL stem cells showed that β-catenin could regulate osteogenic differentiation in inflammatory microenvironments through inhibition of the noncanonical Wnt pathway, which is similar to the regulation by β-catenin of bone homeostasis (Liu et al, 2011).…”
Section: Role Of β-Catenin Signaling In the Periodontal Ligament (mentioning
confidence: 90%
See 1 more Smart Citation
“…It is not clear if β-catenin is responsible for bone maintenance in response to loading, plays a role in mechanotransduction in alveolar bone around teeth, or plays a role in the functions of the PDL. Supporting evidence shows β-catenin expression in the PDL in mice (Lim et al, 2014, Premaraj et al, 2011) in addition to being present in osteocytes and cementocytes. A recent study using PDL stem cells showed that β-catenin could regulate osteogenic differentiation in inflammatory microenvironments through inhibition of the noncanonical Wnt pathway, which is similar to the regulation by β-catenin of bone homeostasis (Liu et al, 2011).…”
Section: Role Of β-Catenin Signaling In the Periodontal Ligament (mentioning
confidence: 90%
“…A recent study using PDL stem cells showed that β-catenin could regulate osteogenic differentiation in inflammatory microenvironments through inhibition of the noncanonical Wnt pathway, which is similar to the regulation by β-catenin of bone homeostasis (Liu et al, 2011). With the osteocalcin-Cre; Wntless fl/fl mice (Wntless, a conserved membrane protein gene dedicated to the secretion of Wnt proteins), a pathological widening of the periodontal ligament space is observed with this elimination of Wntless in teeth (Lim, Liu, 2014). An in vivo study using human PDL cells showed responses to the activation of β-catenin via LiCl, leading to intensive β-catenin nuclear translocation (Premaraj, Souza, 2011).…”
Section: Role Of β-Catenin Signaling In the Periodontal Ligament (mentioning
confidence: 99%
“…Osteocalcin-Cre (OC-Cre) mice were generated with 1.3-kb mouse osteocalcin promoter as described previously (Tan et al 2007). This promoter is different from the OCN-Cre generated with human Osteocalcin promoter (10 kb; Zhang et al 2002) used by Lim et al (2014aLim et al ( , 2014bLim et al ( , 2014c CO/CO mice. The offspring were genotyped by polymerase chain reaction (PCR) analysis using previously described primers (Tan et al 2007;Carpenter et al 2010).…”
Section: Mouse Strainsmentioning
confidence: 99%
“…The removal of Wnt-β-catenin signal in the periodontium leads to severe defects in the PDL and alveolar bone formation (11). In contrast, enhancing Wnt-β-catenin signal activity by removing its antagonist, sclerostin (the product of the Sost gene), results in an increase in alveolar bone volume and reduced PDL width (12).…”
Section: Introductionmentioning
confidence: 99%